The Argentine radioactive waste repository: basic criterio preliminary siting and desing conceptual basic - Beninson, Dan Jacobo; González, Abel Julio; Palacios, Elías; Ciallella, Norberto R. (Comisión Nacional de Energía Atómica; Argentina, 1987)
Fil: Beninson, Dan Jacobo Comisión Nacional de Energía Atómica; Argentina